Uporaba digitalnih osebnih pomočnikov za ljudi z zmanjšanimi zmožnostmi – kratek pregled literature - Debeljak, Mojca (Rehabilitacija (Ljubljana), 2022)
Background: The field of artificial intelligence is expanding into many solutions that make people’s lives easier or more comfortable. In recent years, virtual assistants (VA) are increasingly used, either voice-activated through information and communication devices or through smart speakers. A VA can be used to control the functions of a smart home, find some information, listen to music or to set up reminders. The purpose of this brief literature review is to examine the extent to which VA can improve quality of life for people with disabilities, including older people in terms of independence and loneliness. Methods: The PubMed database was searched using the search string »(virtual assistant or voice assistant or conversational agent or digital assistant) and (people with disabilities or older people) and (social isolation or loneliness or quality of life or independence)«. Papers in English or Slovenian were sought. A systematic review was conducted in accordance with the PRISMA guidelines. Results: In the final analysis, out of the 140 found, 8 papers were included that fulfilled the inclusion criteria. Those papers supported the use of VA for the elderly mainly for setting-up reminders and as »companions« to reduce the feeling of loneliness and social isolation. VA for visually impaired, the motor disabled and older people can bridge some accessibility issues with other devices. No literature in Slovenian language about the use of VA for older people or people with disabilities was found. Conclusion: Voice-activated virtual assistants can contribute to a better quality of life for people with disabilities and older persons. However, there is a need for further research in this area, together with addressing the need for frameworks, guidelines, and regulations. Commercial VA are still not available in Slovenian language.
Keywords: Digital Technology; digitalni osebni pomočnik; Disabled Persons; kakovost življenja; ljudje z zmanjšanimi zmožnostmi; loneliness; older people; osamljenost; quality of life; rehabilitation; social isolation; socialna izoliranost; starostniki; virtual assistant